Corrosion Inhibition of Mild Steel in 0.5 M H2SO4 Solution by Plant Extract of Annona squamosa - Karthikeyan, S.; Syed Abuthahir, S.S.; Samsath Begum, A.; Vijaya, K. (Asian Journal of Chemistry, 2021)
In aqueous solution of 0.5 M H2SO4, the Annona squamosa extract was systematically analyzed to ensure its inhibition mechanism by using potentiodynamics polarization, the weight loss method, and electrochemical impedance spectroscopy (EIS) and its inhibitory effect on mild steel corrosion. For mild steel corrosion in 0.5 M H2SO4 solution, its inhibition efficiency increases and decreases with an increase in its concentration and temperature, respectively. Potentiodynamic polarization analyses revealed that the Annona squamosa behaves as a cathodic inhibitor. In presence of Annona squamosa extract in 0.5 M H2SO4 solution, an increase in the activation energy of corrosion leads to a decrease in the rate of mild steel corrosion. On mild steel surfaces, the adsorption behaviour of the extract conformed to the Temkin isotherm, Langmuir isotherm and Arrhenius equation. The EIS results were correlated with the polarization findings. According to atomic force microscopy (AFM) and scanning electron microscopy (SEM), the inhibition of mild steel corrosion proceeds through the adsorption of the extract on the mild steel surface.